Sustainable tourism on Instagram: insights from Hispanic centennials - Teles, Reinaldo Miranda de Sá; Ramos, Edgar Romario Aranibar; Pacco, Miguel Angel Demetrio Olarte (Sustainability in Debate, 2025)
This study examines sustainable tourism representation on Instagram through #turismosostenible and #turismosustentable, focusing on Spanish-speaking users and posts from 2023. Content analysis reveals a strong emphasis on environmental conservation and sustainable practices, predominantly showcased through natural landscapes and informational content. User-generated content, especially personal photos, dominates the narrative, highlighting the role of grassroots storytelling. However, cultural heritage, community engagement, and certified destinations are notably underrepresented, signalling opportunities to diversify sustainability narratives. Rural and peak-season tourism are the most prominent, while off-peak travel and urban green spaces receive less attention. The limited participation of official tourism boards and non-governmental organisations suggests the need for more robust institutional involvement. This research provides insights into leveraging social media to promote inclusive and impactful sustainability communication, offering practical recommendations to enhance digital strategies.